Exposure to Polycyclic Aromatic Hydrocarbons Among Never Smokers in Golestan Province, Iran, an Area of High Incidence of Esophageal Cancer – a Cross-Sectional Study with Repeated Measurement of Urinary 1-OHPG in Two Seasons - Islami, Farhad; Boffetta, Paolo; van Schooten, Frederik J.; Strickland, Paul; Phillips, David H.; Pourshams, Akram; Fazel-Tabar Malekshah, Akbar; Godschalk, Roger; Jafari, Elham; Etemadi, Arash; Abubaker, Salahadin; Kamangar, Farin; et al. (Frontiers in Oncology, 2012)
Studies have suggested a possible role of polycyclic aromatic hydrocarbons (PAHs) in the etiology of esophageal cancer in Golestan Province, Iran, where incidence of this cancer is very high. In order to investigate the patterns of non-smoking related exposure to PAHs in Golestan, we conducted a cross-sectional study collecting questionnaire data, genotyping polymorphisms related to PAH metabolism, and measuring levels of 1-hydroxypyrene glucuronide (1-OHPG), a PAH metabolite, in urine samples collected in two seasons from the same group of 111 randomly-selected never-smoking women. Beta-coefficients for correlations between 1-OHPG as dependent variable and other variables were calculated using linear regression models. The creatinine-adjusted 1-OHPG levels in both winter and summer samples were approximately 110 μmol/molCr (P for seasonal difference= 0.40). In winter, red meat intake (β= 0.208; P= 0.03), processed meat intake (β= 0.218; P= 0.02) and GSTT1-02 polymorphism (“null” genotype: β= 0.228; P= 0.02) showed significant associations with 1-OHPG levels, while CYP1B1-07 polymorphism (GG versus AA+GA genotypes: β= –0.256; P= 0.008) showed an inverse association. In summer, making bread at home (>weekly versus never: β= 0.203; P= 0.04), second-hand smoke (exposure to ≥3 cigarettes versus no exposure: β= 0.254; P= 0.01), and GSTM1-02 “null” genotype (β= 0.198; P= 0.04) showed significant associations with 1-OHPG levels, but GSTP1-02 polymorphism (CT+TT versus CC: β= –0.218; P= 0.03) showed an inverse association. This study confirms high exposure of the general population in Golestan to PAHs and suggests that certain foods, cooking methods, and genetic polymorphisms increase exposure to PAHs.